(untitled) (Journal of Environmental Science and Natural Resources, 2015)
Lohalia River is one of the most renowned rivers in the coastal Bangladesh and supports diverse fisheries communities. The present study was conducted to identify the types of fishing gears and crafts including their mode of operation in fishing in the Lohalia River during the period from April 2012 to March, 2013. The survey was designed to gather information on the type of gears, process of operation, cost, manpower needed for operation, seasons of operation and principal species of fish caught. The survey revealed that a wide variety of fishing gears were operated throughout the year in the study area for commercial fishing. Some of the gears were selective for a particular species, whereas others account for a number of species caught during operation giving multispecies nature of the fishing. But a number of the fishing gears was found to catch fish irrespective of their size or species and destroys the habitat of the wild species thus causing multiple harms to the biodiversity of the estuary. Training program should be conducted to the fishermen to create awareness of the long-term effects of different fishing gears and to impart knowledge of fishing laws. DOI: http://dx.doi.org/10.3329/jesnr.v7i2.22227 J. Environ. Sci. & Natural Resources, 7(2): 169-175 2014